Modelling a packed-bed latent heat thermal energy storage unit and studying its performance using different paraffins - Andreas Klitou; Theoklitos Klitou; Paris A. Fokaides (International Journal of Sustainable Energy, 2024)
ABSTRACTThermal systems, including those utilising solar energy and waste heat recovery, often have a mismatch between the energy supply and demand. It is crucial to implement a form of Thermal Energy Storage (TES) to effectively utilise the energy source. This study evaluates the thermal performance of a packed bed Latent Heat Thermal Energy Storage (LHTES) unit that is incorporated with a solar flat plate collector. The results show that the time required to charge the tank is reduced by 7% when the porosity is increased from 0.49 to 0.61, and also when the flow rate is raised from 2 to 4 kg/min, the charging time decreases by 2.5%. Additionally, studies were done to investigate the performances of different kinds of paraffin (RT30, RT28HC, WAX, RT58, and P56-58), and compare the heat capacities of each TES tank which resulted in the RT58 TES tank having the highest heat capacity.Abbreviations: BC: boundary conditions; HTF: heat transfer fluid; LHS: latent heat storage; LHTES: latent heat thermal energy storage; PCM: phase change material; SHS: sensible heat storage; TES: thermal energy storage